Mapping ethnicity in nineteenth-century Burma: When ‘categories of people’ (lumyo) became ‘nations’ - Candier, Aurore (Journal of Southeast Asian studies (Singapore), 2019)
Successive wars and the establishment of a border between the kingdom of Burma and British India in the nineteenth century challenged Burmese conceptions of sovereignty and political space. This essay investigates how European, and more specifically Anglo-American, notions of race, nation, and consular protection to nationals, progressively informed the Burmese concepts of ‘categories of people’ (lumyo) and ‘subject’ (kyun). First, I present the semantic evolution of these concepts in the 1820s–1830s, following the annexation of the western Burmese province of Arakan by British India in 1824. Then, I argue that the Burmese concept of lumyo was progressively associated with the European concept of ‘nations’ in the 1850s–1860s, following the annexation of Lower Burma in 1852. Finally, I uncover developments in the 1870s, when British consular protection extended to several freshly categorised ‘nations’, such as Shan, Karenni, and Kachin.